Вирощування монокристалів та уточнення кристалічної структури Cu3SbSe3 - Чорба Оніка; Chorba Onika; Філеп Михайло; Filep Mihály; Filep Mykhailo; Погодін Артем; Pogodin Artem; Малаховська Тетяна; Malakhovska Tetyana; Сабов Мар’ян; Szabó Marján; Sabov Marjan (My University, 2022)
Резюме. Вперше здійснено успішне вирощування монокристала тернарного селеніду Cu3 SbSe3 з інконгруентним характером плавлення методом спрямованої кристалізації. Одержаний монокристал досліджено диференційно-термічним та рентгенівським фазовим аналізами. Використовуючи повнопрофільний метод Рітвельда, здійснено уточнення кристалічної структури. Встановлено, шо Cu3 SbSe3 володіє каркасною структурою та кристалізується в орторомбічній сингонії, ПГ Pnma з параметрами ґратки a = 7.9668 Å, b = 10.65870 Å, c = 6.8207 Å, Z = 4.

Abstract. The technology of thermoelectric converters, based on the Peltier and Seebeck effects, provides a reversible process of converting thermal and electrical energy. This opens up prospects for the creation of both thermoelectric coolers and thermoelectric generators. The most widely studied class of thermoelectric materials are complex chalcogenides. In recent years, copper-containing chalcogenides have been actively researched as new highly effective and ecologically friendly thermoelectric materials. The Cu–Sb–Se ternary system are characterized by the existence of three phases CuSbSe2 , Cu3 SbSe3 and Cu3 SbSe4 . Among these compounds, the Cu3 SbSe3 phase is characterized by the lowest thermal conductivity. The synthesis of the Cu3 SbSe3 polycrystalline alloy was carried out using high purity elementally components. The synthesis was carried out in vacuumed quartz ampoules by a one-temperature, two-stage process. Taking into account the incongruent melting of Cu3 SbSe3 , the single crystal growth was carried out by the method of vertical zone crystallization from a solution-melt in vacuumed conical quartz ampoules. As a result, the grown single crystal was dark gray color with metallic luster, without defects with length ~ 40 mm and diameter 12 mm. Obtained single crystalline sample of Cu3 SbSe3 was investigated by DTA method. The heating curve contains one endothermic effect at 530°С, which corresponds to the process of peritectic decomposition of Cu3 SbSe3 . The effect corresponding to the melting of all components in the quartz container is not fixed. However, it is clearly visible on the cooling curve at 712 °С. The exothermic effect of crystallization of Cu3 SbSe3 (503 °С) is clear and sharp and is observed with supercooling ΔТ = 27 °С. To confirm the single crystallinity of grown Cu3 SbSe3 sample, an XRD analysis of the natural surface was carried out. The diffraction pattern shows two clear and narrow diffraction peaks corresponding to the (200) and (400) planes at angles of 22.27° and 45.42°, respectively. The crystal structure of the obtained Cu3 SbSe3 single crystal was investigated by XRD analysis using the Rietveld full-profile refinement method. Established that Cu3 SbSe3 crystallize in orthorhombic crystal system, SG Pnma with lattice parameters: a = 7.9668 Å, b = 10.65870 Å, c = 6.8207 Å, Z = 4.
Crystals growth and refinement of the Cu3SbSe3 crystal structure
Редколегія: https://ucj.org.ua/index.php/journal/about/editorialTeam
Keywords: селеніди; монокристали; кристалічна структура